Cooperation With Arbuscular Mycorrhizal Fungi Increases Plant Nutrient Uptake and Improves Defenses Against Insects - Yu, Lu; Zhang, Wantong; Geng, Yiyi; Liu, Kesi; Shao, Xinqing (Frontiers in Ecology and Evolution, 2022)
Plants have evolved various defense mechanisms to cope with biotic and abiotic stresses. Cooperation with microorganisms, especially arbuscular mycorrhizal fungi (AMF), strengthens the defense capabilities of host plants. To explore the effect of AMF on the growth of Elymus and the defenses against locust feeding, we designed a two-compartment device to connect or cut the mycelia and roots. We used this to investigate communication cues and pathways between donor and receiver plants. We found that AMF significantly increased nitrogen content, but decreased and the carbon to nitrogen ratio of donor plants and receiver plants and decreased carbon content of both. After common mycorrhiza network (CMN) establishment with AMF between the two chambers, inoculations of donor plants challenged by locusts caused enhancement in four defense-related enzymes (lipoxygenase, polyphenol oxidase, phenylalanine ammonia-lyase, and β-1,3-glucanase) in the receiver plants. The main components of volatile organic compounds emitted by receiver plants were terpenoids. The findings indicated that AMF could not only improve plant growth but also activate the defense response of plants to insect feeding. Four defense enzymes, volatile organic compounds, and carbon and nitrogen content were involved in the defense response, and the mycelial network could act as a conduit to deliver communication signals.